(-16)x(2)-(-10)x(4)=

Simple and best practice solution for (-16)x(2)-(-10)x(4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-16)x(2)-(-10)x(4)= equation:


Simplifying
(-16) * x(2) + -1(-10) * x(4) = 0

Reorder the terms for easier multiplication:
-16 * 2x + -1(-10) * x(4) = 0

Multiply -16 * 2
-32x + -1(-10) * x(4) = 0

Reorder the terms for easier multiplication:
-32x + -1 * -10 * 4x = 0

Multiply -1 * -10
-32x + 10 * 4x = 0

Multiply 10 * 4
-32x + 40x = 0

Combine like terms: -32x + 40x = 8x
8x = 0

Solving
8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '8'.
x = 0

Simplifying
x = 0

See similar equations:

| 13x+10=-29-39x | | 10r^3=250r | | x^5-2x^4-12x^3+24x^2+35x-70= | | 4(3n-2)=5-2(n-1) | | x^5-2x^4-12x^3+24x+35x-70= | | 4k+1=3 | | 7(4x+10)=294 | | -3(5x+5)=-150 | | -4(-7x-8)=228 | | 3(7x+5)=-111 | | 2s^2=9s+5 | | 3m-5=17 | | x+1.5x+1.25x=3700 | | 6(-7+5x)=288 | | 3v(10v+7)=0 | | 7(-3+5x)=-336 | | x+1.5x+.75x=3700 | | 7(-3+5x)=288 | | -2(5x+4)=-128 | | 228-5x=31x+20 | | 12-10x=92-38x | | 79-4x=10x+23 | | -94-10x=9x+20 | | 6(3+7x)=228 | | 2(-10-2x)=-4 | | 208-2x=34x+20 | | -94-10x=9x+38x | | 2x+10=-50-10x | | -9-5x=11-10x | | 5(6+6x)=30 | | 2x+13=-37-8x | | -17=-5x+7x+7 |

Equations solver categories